Conditional Decisions as Instrument Guarding the Supremacy of the Constitution (Analysis of conditional decisions of Indonesian Constitutional Court in 2003 – 2017) - Safa'at, Muchamad Ali; Eko Widiarto, Aan (Faculty of Law, Universitas Brawijaya, 2021)
The function of the Indonesian Constitutional Court as the guardian of the constitution is mainly conducted through the judicial review authority. Since 2003 to April 2021, the Constitutional Court has received and decided 1392 petitions over judicial review. In its dictums, the Constitutional Court often declares conditionally constitutional or conditionally unconstitutional (conditional decision). Conditional decision is a decision of the Court that declare the reviewed norm conditionally constitutional or unconstitutional. The norm is constitutional if interpreted pursuant to the Court interpretation, or the norm is unconstitutional if interpreted in certain ways. This research is aimed to investigate the criteria of judicial review decisions which declares conditionally constitutional and conditionally unconstitutional in accordance with the characteristics of norms of the law reviewed. The analysis was limited to the Court decisions from 2003 to 2017. The research result indicates that distinguishing characters of norms reviewed have no correlation with the option between conditionally constitutional or conditionally unconstitutional. Â Conditionally Constitutional Decision was used by the court before replaced by Conditionally Unconstitutional Decision due to the weakness of decision implementation. For conditionally unconstitutional decisions are connected to the substance of the decision which create new norm that replace, limit, or elaborate reviewed norm. Conditional decision is still required as a consequence of the following three aspects: enforcement of the supremacy of the constitution, presumption of validity, and strengthening the execution of Constitutional Court decisions.